Adverse childhood experiences (ACE) pipeline to prison? : prevalence of ACEs and its effects on quality of life in Icelandic prison and drug rehabilitation population - Jónína Sigrún Birgisdóttir 1989- (2022)
Adverse childhood experiences (ACE) have been identified as a major contributing factor to future negative health outcomes, which can lead to a lower quality of life and are often linked with both substance abuse and imprisonment. ACEs are prone to have lasting, negative effects on health, life opportunities regarding career and education, as well as overall well-being. This is the first study aimed to examine the prevalence and effects of ACEs and their effects on the quality of life in prison and drug rehabilitation populations in Iceland, as well as examining the most common types of ACEs experienced. Two hypotheses were examined: 1) That there is no difference in the prevalence of ACEs among individuals serving a prison sentence and individuals in alcohol and drug rehabilitation; 2) That there is a correlation between higher ACEs and lower quality of life. A total of 96 persons participated in the study, 53 participants serving a prison sentence and 43 in rehabilitation. The research was conducted at various prisons, and alcohol and drug rehabilitation in Iceland. The average ACE score for the study sample was 4.9; there was not a significant difference in the prevalence of ACEs between groups. The most common types of ACEs experienced were witnessing domestic abuse (97.5%) and/or physical neglect (92.2%). The results concluded that a higher ACE score correlated with a decrease in quality of life. Consistent with the ACE literature, the results imply that the prevalence of ACEs is high among the prison and drug rehabilitation population in Iceland.